PENGEMBANGAN MEDIA PROMOSI KESEHATAN VIDEO IKLAN LAYANAN MASYARAKAT MENGENAI PENCEGAHAN OBESITAS PADA REMAJA KOTA BANDUNG (Politeknik Kesehatan Kemenkes Bandung, 2021)
Obesity in adolescents triggers the onset of various degenerative diseases until death. Prevention of obesity in adolescents can be done by promoting health media, especially public service advertising videos to increase knowledge, awareness of attitudes to problems, as well as get a good image in the eyes of students. The purpose of this study is the production of health promotion media Public Service Advertising Videos on The Prevention of Obesity in Adolescents. The research design used a mixed-method with exploratory sequential mixed methods design. Starting with qualitative research with interviews with 7 students. Furthermore, quantitative research was conducted through questionnaires to 71 students. The results of the exploration of the media model of public service advertising media on the prevention of obesity as a medium of Health Promotion in adolescents obtained the result that adolescents better understand the material through videos such as public service advertisements themed on health education, especially discussing the causes of obesity and ways of prevention of obesity such a diet with a duration of about 2-3 minutes that is not too much text but more images and music/sound.The results showed that the results of media validation from material experts were 67% in the appropriate category, media experts were 96.36% in the very feasible category and trials to users were 86.22% in the very feasible category while increasing knowledge to 71 respondents regarding obesity prevention increased from the pre-test result of 56.62% to 74.08% with the result of the T-test known the sig value. (2-Tailed) is 0.000<0.005 meaning that health education through public service advertisement videos on obesity prevention.